John Searle’s Naturalism as a Hybrid (Property-Substance) Version of Naturalistic Psychophysical Dualism - Сепетий, Дмитро Петрович; Sepetyi, Dmytro (My University, 2019)
The article discusses the relationship between John Searle’s doctrine of naturalism and various forms of materialism and dualism. It is argued that despite Searle’s protestations, his doctrine is not substantially different from the epiphenomenalistic property dualism, except for the admission, in his later works, of the existence of an irreducible non-Humean self. In particular, his recognition that consciousness is unique in having an irreducible first-person ontology makes his disavowal of property dualism purely verbalistic. As for epiphenomenalism, Searle’s explanation of how consciousness can be efficacious without violating the causal closure of the physical, by analogy with the causal efficacy of the higher level properties of physical objects that are supervenient on the microphysical, confuses causality and constitution (causal and constitutive supervenience). It is also argued that Searle’s recognition of the existence of an irreducible non-Humean self that is responsible for decision-making sits badly both with his (property dualistic) view that conscious mental states are irreducibly first-personal states of the brain (rather than of the self) and with his (epiphenomenalistic) view that consciousness has no causal power in addition to that of the underlying neurobiology
Keywords: Consciousness; naturalism; materialism; dualism; epiphenomenalism